2002
DOI: 10.1021/ie020084f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of MDI from Dimethyl Carbonate over Solid Catalysts

Abstract: The catalytic synthesis of methylene diphenyl-4,4′-diisocyanate (MDI) consists of three steps. Starting from the catalytic reaction of aniline and dimethyl carbonate (DMC), methyl phenyl carbamate (MPC) is formed. Then MPC condenses with formaldehyde to produce dimethyl methylene diphenyl-4,4′-dicarbamate (MDC). Last, MDC is decomposed to MDI. For the first step, the properties of supported zinc acetate catalysts on different supports have been examined. Supported zinc acetate catalyst on activated carbon (AC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 1 publication
2
33
0
1
Order By: Relevance
“…In summary, the results showed that the catalysts with surface Lewis acid sites with higher acid strength favored N-substituted carbamates using alkyl carbamates or aromatic carbamates as carbonyl source. [47] ZnCl 2 Nitro benzene, 100 ℃, 5 h, 9∶1 81 [48] ZnCl 2 /AC Nitro benzene, 140 ℃, 3 h, 4∶1 43 [49] 50% H 2 SO 4 H 2 O, 90 ℃, 2 h, 5∶1 74 [50] Amberlyst 15 CH 3 CN,75 ℃, 4 h, 4∶1 63 [51] Silicotungstic acid Diethylene glycol dimethyl ether, 100 ℃, 4.5 h, 8∶1 63 [52] Phosphotungstic acid Diethylene glycol dimethyl ether, 110 ℃, 4.5 h, 5∶1 65 [53] [ [54] Hβ DMC, 160 ℃, 3 h, 4∶1 76 [55] CO 2 as carbonyl source…”
Section: Alkyl Carbamates As Carbonyl Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…In summary, the results showed that the catalysts with surface Lewis acid sites with higher acid strength favored N-substituted carbamates using alkyl carbamates or aromatic carbamates as carbonyl source. [47] ZnCl 2 Nitro benzene, 100 ℃, 5 h, 9∶1 81 [48] ZnCl 2 /AC Nitro benzene, 140 ℃, 3 h, 4∶1 43 [49] 50% H 2 SO 4 H 2 O, 90 ℃, 2 h, 5∶1 74 [50] Amberlyst 15 CH 3 CN,75 ℃, 4 h, 4∶1 63 [51] Silicotungstic acid Diethylene glycol dimethyl ether, 100 ℃, 4.5 h, 8∶1 63 [52] Phosphotungstic acid Diethylene glycol dimethyl ether, 110 ℃, 4.5 h, 5∶1 65 [53] [ [54] Hβ DMC, 160 ℃, 3 h, 4∶1 76 [55] CO 2 as carbonyl source…”
Section: Alkyl Carbamates As Carbonyl Sourcementioning
confidence: 99%
“…In 2002, Zhang et al [82] employed zinc powder as catalysts for the synthesis of MDI using nitrobenzene-THF and di-n-octyl sebacate (DOS) as the mixed solvent and heat carrier, respectively. The highest MDI yield was 87.3% at ca.…”
Section: Thermal Cracking Of N-substituted Carbamates In Organic Solvmentioning
confidence: 99%
“…Preliminary investigations were conducted employing homogeneous catalysts and comparing their reactivity with the one of zinc acetate, extensively investigated for the carbamoylation of aniline [12][13][14][15]. Scheme 2 shows the mechanism of carbamoylation of aniline via DMC chemistry.…”
Section: Homogeneous Catalystsmentioning
confidence: 99%
“…According to the best results obtained for the carbamoylation of aniline employing homogeneous catalysts (Table 2) and to the bibliographic data available, lead, tin, copper, zinc, and bismuth salts were selected to be supported on silica or alumina [11][12][13][14]. Supported heterogeneous catalysts were investigated with the intent to easily recover the catalyst at the end of the reaction without using any timewasting separation and/or purification needed for the homogeneous catalysts.…”
Section: Heterogenized Catalystsmentioning
confidence: 99%
“…Recently, several examples of carbamoylation of aniline, 9 4,4′-methylenedibenzenamine 10 (for the synthesis of methylene diphenyl diisocyanate, MDI) and 2,4-diaminotoluene 11 (for the synthesis of toluene diisocyanate TDI) have been reported by DMC chemistry in the presence of either homogeneous or supported catalysts. An example is the efficient carbamoylation of 2,4-diaminotoluene (DAT) by gold-catalyzed phosgene-free synthesis.…”
mentioning
confidence: 99%